2022
DOI: 10.3390/microorganisms10020387
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Uveitis in Horses and New Insights in Its Leptospiral Biofilm-Related Pathogenesis

Abstract: Uveitis is a sight-threatening eye disease in equids known worldwide that leads to considerable pain and suffering. By far the most common type of uveitis in Germany and neighboring countries is classical equine recurrent uveitis (ERU), which is caused by chronic intraocular leptospiral infection and is the main cause of infectious uveitis in horses. Other infectious causes are extremely rare and are usually clinically distinguishable from ERU. ERU can be treated very effectively by vitreous cavity lavage (vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 429 publications
(764 reference statements)
0
50
0
Order By: Relevance
“…This was based on an apparent lack of detectable spirochetes in the eye, evidence of molecular mimicry in some studies, poor response to antimicrobial therapy, and response to glucocorticoid treatment. 37 However, a 2021 study 38 from Germany that examined equine eyes after vitrectomy indicated that biofilm formation within the eye may explain resistance to systemic antimicrobial therapy.…”
Section: Leptospirosis In Animalsmentioning
confidence: 99%
“…This was based on an apparent lack of detectable spirochetes in the eye, evidence of molecular mimicry in some studies, poor response to antimicrobial therapy, and response to glucocorticoid treatment. 37 However, a 2021 study 38 from Germany that examined equine eyes after vitrectomy indicated that biofilm formation within the eye may explain resistance to systemic antimicrobial therapy.…”
Section: Leptospirosis In Animalsmentioning
confidence: 99%
“…The preliminary report and a careful clinical and ophthalmologic examination allow an etiologic diagnosis of uveitis in most cases [1]. In addition to traumatic uveitis, which typically occurs only once [2,3], there is also chronic insidious uveitis (e.g., uveitis in leopard coat pattern horses [3][4][5], phacogenic uveitis [6], chronic iritis [1,7] or tumor-associated uveitis [8][9][10], therapy-resistant uveitis (e.g., in intraocular parasitosis [11,12]) or septicemia-associated uveitis (most frequently in foals with rhodococcosis [13]). Regardless of etiology, each acute uveitis episode requires well-aimed and meticulous conservative therapy [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…In chronic uveitis, various therapeutic options have been described to prevent progressive damage to intraocular structures and further relapses (e.g., subscleral cyclosporine implants [14] or intravitreal gentamicin injections [15][16][17][18][19]), which, however, should be applied selectively and depending on the etiology of the uveitis [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations